Mandibular Fractures - MAKUNGU, Alain Patrick; MIKEMOU, Frida NIMY MBUNGU; EYA, Lyvana Hornelia ZUE; MANDZA, Léila Carmen (Mandibular Fractures, Edition 1, 2025)
Introduction: The mandible is the only symmetrical, medial, mobile bone of the face located on the lower and anterior level of the face. It is susceptible to trauma, including fractures. General: The mandible is composed of three distinct regions that converge at the mandibular angle, and predominates in young adult males (75.5%) [13] The mean age of the subjects was 22.3 ± 12 years (range: 2–72 years), with MVAs representing the main etiology (47%) [15]. Mandibular fractures can be partial or total, isolated or associated, and parasymphyseal fractures are the most common (39%) [15]. Clinical Evaluation: Facial edema was predominant in 90.4% [15]. Furthermore, 66.7% of patients [42] with bifocal fractures undergo orthopontomograms. CT allows for precise analysis of the fracture lines' location, and the different fragments displacements. Treatment: The management of mandibular fractures encompasses a range of treatment modalities, including emergency, skeletal and complication treatments. Complications occurred in 3.1% of cases, with a success rate of 95.4% [25]. Conclusion: Mandibular fractures are a prevalent type of fracture that occurs in adolescent males. CT is the reference examination. The most common fracture is that of the parasymphysis, and its management must be expeditious in order to avoid complications.